PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, INDEPENDENSI DAN KOMITMEN ORGANISASI PADA KINERJA AUDITOR - Ratnantari, I Gusti Agung Malyani; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of intellectual intelligence, emotional intelligence, spiritual intelligence, independence, and organizational commitment on performance auditor in public accounting firm in Bali. This research was conducted at seven public accounting firms in Bali which has been listed in the Indonesia Institute of Certified Public Accountants (IAPI). The samples used were 38 respondents with purposive sampling technique. The data collection was conducted by questionnaire. The data analysis technique used to test the hypothesis in this study is Multiple Linear Regression Analysis. The results of this study suggest that intellectual intelligence, emotional intelligence, spiritual intelligence, independence, and organizational commitment positively affects the performance of auditors.This shows that the increasing intellectual, emotional intelligence, spiritual intelligence, independence, and commitment to the organization, the auditor's performance is increasing as well.
Keywords: Performance Auditor, Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Independence, Organizational Commitment